Biological and chemical hazards, legislation, detection techniques, and their availability in exporting rainbow trout (Oncorhynchus mykiss) and fan conch (Argopecten purpuratus) from Peru - Monsalve Tequen, Eveling (2023)
The study's objective was to describe the biological and chemical hazards that limit the export of rainbow trout and fan conch in Peru through regulatory evidence and background information from the literature, as well as to cite detection techniques and their availability in Peru. To this end, a list of current regulations related to biological and chemical hazards in Peru, Europe, and the United States was made, finding a close resemblance between the hazards and their maximum permissible limits. The export cases rejected between 2015 and 2020 were compiled by searching for information through four sources: SANIPES (Fishery Health Agency) safety report, request to SANIPES, Web IntradeBid, and international WEB portals (OASIS-FDA from the United States and RASFF from Europe), identifying only one case of rejection with cause of biological hazard (Salmonella) in fan shell during 2015. Finally, detection methods and their availability are mentioned. In all cases, the laboratories that perform the tests must be accredited by ISO/IEC 17025, which guarantees the reliability of the tests and foreign trade; in addition, in the case of Peru, SANIPES is responsible for publishing the list of approved laboratories and methods.